Study of Light Wavelength and Some Concentration Salts in Growth Medium on Growth, Protein and Nitrogen Content of Hapalosiphon arboreus 3OW05S02 - Fatin Al-Rashidy; Yousef Al-Shaheree (College of Education for Pure Sciences, 2021)
Local isolation was obtained from cyanobacteria fixing atmospheric nitrogen, and isolated from the local environment of the city of Mosul (Tigris River forest area). A molecular diagnosis of this isolate was carried out for the purpose of genetic diagnosis, and it was found that it is a pure isolate of cyanobacteria Hapalosiphon. arboreus 3OW05S02. And the phenotypic diagnosis coincided with autopsy.This isolation was grown laboratory in the medium of Chu10. As for the change of wavelengths of light, The results showed that the best wavelength of light was (620-750)nm for red light, the biomass is (770) mg / liter, the protein content is (230) mg / liter, the nitrogen content is (119) mg / liter. Also I studied a number of mineral elements that affect growth and nitrogen fixation, and it was found that the best concentration of potassium phosphate K2HPO4 is (50)mg/liter, as recorded the biomass is (802) mg / liter, the protein content is (202)mg / liter, the nitrogen content is (107) mg / liter. When adding Ca(No3)2 to the medium with different concentrations and comparing them without adding this material to the medium, the best concentration was (60) mg/liter, the biomass is (790) mg/liter, the protein content is (138) mg /liter, the nitrogen content is (74) mg /liter.